Body/sex/work intimate, embodied and sexualized labour - Wolkowitz, Carol; Cohen, Rachel Lara; Sanders, Teela; Hardy, Kate (Houndmills, Basingstoke, Hampshire Palgrave Macmillan, 2013)
Body/Sex/Work focuses on the intimate, embodied and sexualized labour that occurs within body work and sex work. Bringing together an internationally renowned group of academics, it explores, empirically and theoretically, labour processes, workplace relations, regulation and resistance in some of the many work sites that make up the body work and sex work sectors. The book makes a key contribution to research recognising the embodiment of labour and the body, reframing the key questions in critical studies of work and employment.
The body/sex/work nexus : a critical perspective on body work and sex work / Rachel Lara Cohen ... [et al.] -- Touching moments : an analysis of the skilful search for dignity within body work interactions / Marek Korczynski -- Equal to any other, but not the same as any other : the politics of sexual labour, the body and intercorporeality / Kate Hardy -- Legal constructions of body work / Ann Stewart -- Gender, emotional labour and interactive body work : negotiating flesh and fantasy in sex workers' labour practices / Barbara G. Brents and Crystal A. Jackson -- The frontline costs of the southern cross decline / Joe Greener -- Hairdressing/undressing : comparing labour relations in self-employed body work / Teela Sanders, Rachel Lara Cohen and Kate Hardy -- Altered bodies, engineered careers : a comparison of body technologies in corporate and do-it-yourself pornographic productions / Lori L. Fazzino -- From erotic capital to erotic knowledge : body, gender and sexuality as symbolic skills in phone sex work / Giulia Selmi -- 'What does a manicure have to do with sex?' Racialized sexualization of body labour in routine beauty services / Miliann Kang -- Touch in holistic massage : ambiguities and boundaries / Carrie Purcell -- Racing bodies / Janet Miller -- Body work and ageing : the biomedicalization of nutrition practices / Giulia Rodeschini -- Getting the bodies of the workers to the bodies of the clients : the role of rotas in domiciliary care / Gemma Wibberley -- Saliva, semen and sanity : flat-working in Hong Kong and bodily management strategies / Olive Cheung.
Includes bibliographical references and index.
Keywords: Women -- Employment; Work; Labor